Development of Ulva lactuca Nori-like Products with Heritage Flavors from Traditional Fermented Products from Riau - M. Haekal Tiftazani; Joko Santoso; Wahyu Ramadhan (Jurnal Ilmiah Kesehatan (JIKA), 2026)
The demand for nori in Indonesia continues to rise; however, the limited availability of local raw materials, such as Porphyra sp., necessitates the development of alternative products based on other types of seaweed. This study aimed to evaluate the effects of adding terasi and rusip to the formulation of nori-like products made from Ulva lactuca on sensory, physical, and chemical characteristics. A Completely Randomized Design (CRD) was employed, consisting of one factor with four levels and three replications. The treatments involved varying formulations of terasi:rusip ratios (1:4, 2:3, 3:2, and 4:1). The best formula was determined based on hedonic sensory evaluation by trained panelists. The selected formula was then subjected to proximate analysis and color profiling. The results revealed that the best formulation was the 3:2 terasi:rusip ratio, which achieved the highest hedonic score for overall acceptability (4.5, categorized as "very liked"). Proximate analysis of the best formula showed a protein content of 18.14%, moisture content of 2.46%, ash content of 20.53%, fat content of 10.28%, and carbohydrate content of 48.59%. The dominant amino acids in the nori-like product were glutamic acid, aspartic acid, and alanine. Color profile analysis indicated an L* value of 41.46 (high brightness), a* value of -9.33 (green dominance), and b* value of 30.32 (yellowish tendency). These findings suggested that the combination of terasi and rusip enhances the sensory quality and physicochemical characteristics of nori-likeproducts while offering potential for the development of local nori products with distinctive Indonesian flavors.